Quantifying the health impact of crop breeding: Revisiting the Disability-Adjusted Life Years Approach - Lenaerts, Bert (MedRxiv, 2024)
Crop breeding, through methods like biofortification, plays a crucial role in increasing agricultural yields, contributing to a stable and healthy food supply by boosting the micronutrient content of staples, which is pivotal for combating chronic and hidden hunger, especially in rural areas. This shift towards improved nutrition can be sustainably integrated into regular diets, marking a significant stride in public health. The burden of hunger and its consequences on health are increasingly quantified using the Disability-Adjusted Life Years (DALYs) approach, which merges years of life lost and years lived with disability, offering a comprehensive view of health impacts and aiding in resource allocation despite its complexity and subjective nature. A practical formula for quantifying the health impact of biofortification was introduced by Stein et al. (2005) and Zimmermann and Qaim (2004). This entails calculating the efficacy or relative reduction in hunger burden based on the current and post-intervention nutrient intake against the recommended dietary allowances. As data on consumption and recommended intake levels are variable and not readily available, this paper proposes relying on relative estimates to bridge the data gaps and uncertainties, thus streamlining the quantification of crop breeding's impact on diets and overall health.